SIMULTANEOUS INTERPRETING USED IN “THE SAMSUNG GALAXY S24 AUTOMATICALLY TRANSLATES CALLS VIA AI” VIDEO ON RAPPLER’S YOUTUBE CHANNEL - Kurnia Septiana Putri; Ramadan Adianto Budiman (PT Akselerasi Karya Mandiri, 2024)
The existence of this scientific article aims to provide a brief description of the position of translation in the phenomenon of globalization, which is inseparable from technological advances and human mobility that demand a connection between language and culture. Therefore, to discuss the world of interpreting further, the researcher chose the title